Transforming Environmental Knowledge into Green Purchase Intention Among University Students in Yogyakarta - Andreas Mahendro Mahendro Kuncoro; Nurhadistya Alyfakhry Deamahdyka Rayhananda Sabandi; Eric Ohara; Melvin Rahma Sayuga Subroto (JTI: Jurnal Teknik Industri, 2026)
This research aims to examine how environmental knowledge is transformed into green purchase intention among university students in Yogyakarta, Indonesia. Although previous green product studies have examined environmental knowledge, awareness, eco-innovation, and green product perception as determinants of purchase intention, the sequential mechanism through which knowledge becomes intention remains underexplored. University students are relevant because they are exposed to environmental knowledge through higher education, campus activities, digital media, and sustainability discourse. This issue is important in Yogyakarta, where a strong higher-education ecosystem coexists with persistent waste-management problems. This study proposes a sequential knowledge-transformation model linking environmental knowledge, environmental awareness, perceived eco-innovation, perceived green product, attitude toward green products, and green purchase intention. A student-based subset of a previous green product survey dataset involving 187 university students was analyzed using PLS-SEM and IPMA. The results show that all direct relationships are positive and significant. Attitude toward green products has the strongest effect on green purchase intention, while perceived eco-innovation strongly influences perceived green product. The sequential indirect effect from environmental knowledge to green purchase intention is supported. IPMA shows that attitude has the highest importance, whereas environmental knowledge has the lowest performance. These findings suggest that universities and green product stakeholders should strengthen practical environmental literacy and credible green product communication. Keywords: environmental knowledge; green purchase intention; perceived green product; university students; PLS-SEM-IPMA